Kundanalys av tryckpappersförbrukare i Finland - Jerenius, Oskar (2010)
The negative trend of newspapers reading gives the owner of several paper manufacturing companies in the West worries. Producers should be more concern to strengthen their market positions in order to maintain profitability in the paper mills. Holmen Paper is a medium sized paper mill company with all of their production in Europe. Sales are mainly made to printing companies operating in European countries. In order to strengthen their economic strength Holmen Paper needs to increase the market share in markets where they have the greatest profit margins. These markets are market near their production lines such as Sweden, Norway, Denmark and Finland. The Finnish paper market is one of Holmen Papers weakest markets and therefore the greatest potential to increase.